2015
DOI: 10.1021/acs.jproteome.5b00470
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Response of the Human Urinary Metabolome to Brief Maximal Exercise by a Combination of RP-UPLC-MS and 1H NMR Spectroscopy

Abstract: The delineation of exercise biochemistry by utilizing metabolic fingerprinting has become an established strategy. We present a combined RP-UPLC-MS and (1)H NMR strategy, supplemented by photometric assays, to monitor the response of the human urinary metabolome to short maximal exercise. Seventeen male volunteers performed two identical sprint sessions on separate days, consisting of three 80 m maximal runs. Using univariate and multivariate analyses, we followed the fluctuation of 37 metabolites at 1, 1.5, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 46 publications
6
48
0
5
Order By: Relevance
“…Changes indicate increased degradation of purines, carbohydrates, proteins, and amino acids with exercise. These results are in accordance with previous work from our group and others on the changes of the urinary metabolic fingerprint after acute exercise [45,46]. However, the present study included individuals with MetS, in addition to healthy non-athletes, three different exercise modes, and a 24 h follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Changes indicate increased degradation of purines, carbohydrates, proteins, and amino acids with exercise. These results are in accordance with previous work from our group and others on the changes of the urinary metabolic fingerprint after acute exercise [45,46]. However, the present study included individuals with MetS, in addition to healthy non-athletes, three different exercise modes, and a 24 h follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, sucrose which increases in night-time samples in our study, likely due to dietary intake, was proposed as a marker of sugar intake in an obese population28. Other metabolites are established to vary throughout the day due to physiological processes such as creatinine which fluctuates depending on glomerular filtration rate and physical activity2930. N- methyl nicotinamide in several studies was also shown to be high in the morning before breakfast, probably due to reduced enzymatic activity following fasting31.…”
Section: Discussionmentioning
confidence: 52%
“…The physiological [17] and metabolic [18] alterations derived from training are well-established and there are several studies which investigated these through a metabolic profiling approach. In both humans [19,20,21,22,23,24] and rodents [25,26,27,28,29,30,31,32,33,34], metabolomics-based studies decipher changes in amino acids, carbohydrates’ metabolism, Krebs cycle and lipids’ metabolism and other intermediates of biochemical pathways featured as energy providers. These findings on altered metabolism derived from exercise on humans were recently reviewed [35].…”
Section: Introductionmentioning
confidence: 99%